An unexpected temporary suppression of lactation after a local corticosteroid injection for tenosynovitis. (December 2013) - Babwah, Terence J.; Nunes, Paula; Maharaj, Rohan G.
Abstract Introduction: Intra-lesional glucocorticosteroid (GCS) injections are used widely for painful musculoskeletal conditions in general practice. Case: A 26 year old female, was given an intra-lesional injection of 24 mg methyl prednisolone acetate (MPA) with 15 mg lidocaine for treatment of DeQuervain's tenosynovitis. She was six weeks postpartum and predominantly breast feeding. Lactation was suppressed at approximately 30 h post injection and this persisted for a period of approximately 36 h before spontaneous resumption of milk production. Lactation returned to normal 90 h after the injection. Discussion: Studies done in lactating animals have shown that injected GCS have led to a reduction of milk production, but there is limited data on these injections in lactating humans. The dose of GCS administered and the site of the GCS injection appear to contribute to this phenomenon. Very large doses of GCS have caused suppression of lactation in humans as opposed to low doses of GCS. Injections of GCS into areas of the body subjected to high activity level like the knee or wrist could lead to greater systemic absorption of GCS than GSC administered to body sites with lower physical activity like the shoulder. Conclusion : Local injection of MPA reversibly suppressed lactation in a young woman for a period of 24–48 h. Doctors using injectable GCS in lactating women should apprise patients of this possibility. Mothers can take precautions like expressing and storing enough breast milk to cover this period prior to receiving these injections.